An experimental study and computational validation of waste heat recovery from a lab scale ceramic kiln using a vertical multi-pass heat pipe heat exchanger. (1st October 2020) - Brough, Daniel; Mezquita, Ana; Ferrer, Salvador; Segarra, Carmen; Chauhan, Amisha; Almahmoud, Sulaiman; Khordehgah, Navid; Ahmad, Lujean; Middleton, David; Sewell, H. Isaac; Jouhara, Hussam
Abstract: The development of waste heat recovery technologies has surged as a result of climate change initiatives, which require energy intensive industries to curb their emissions and lower energy consumption. Installing heat pipe heat exchangers has proven to be a reliable and effective method of recovering waste heat due to their passive operation, superconductive properties and small footprint. This paper highlights the application of a vertical multi-pass heat pipe heat exchanger to a lab scale ceramic kiln system used to transfer heat from the kiln exhaust to water. The innovative heat pipe heat exchanger exists as a novel variable unit able to recover heat energy for a range of inlet temperatures and flow rates. The installed unit has shown a heat recovery rate of up to 63 kW. A range of exhaust gas temperatures from 135 to 270 °C were trialled at varying heat source and sink mass flow rates. The results of the experiments as well as simulation results using a model built using the software TRNSYS are given. The investigation has confirmed that the TRNSYS simulation results agree well with the experimental results. Additionally, return on investment analysis predicted 33 months payback for a theoretical full-scale unit preheating water for space heating.